Preparation/characterization of plasticized poly ( Lactic acid) for packaging applications - Santhoskumar, A. U.; Ramkumar, A. (My University, 2014)
In this research an attempt is made to modify the brittle poly (Lactic acid) (PLA) into flexible PLA by adding Poly (Butylene Succinate) (PBS), Poly (Ethylene Glycol) (PEG) and Ricinoleic acid (R.ACID) as a plasticizer. Various plasticizers with different weight % of plasticizers - 10%, 20% and 30% in wt% for PLA/PBS, 5, 10 and 15% for PLA/PEG and PLA/R.ACID are used to make sheets. With the addition of plasticizers, the failure mode changes from brittle fracture of neat PLA to ductile fracture of the plasticized PLA, upon plasticization glass transition temperature (Tg) decreased from 62°C to 46ºC. With the increase of plasticizers content, the tensile strength and modulus of the PLA decreased slightly while the elongation at break and toughness of plasticized PLA were increased (from 5.7 to 11.9%). Further tear strength increased to maximum value of 36 MPa. SEM analysis confirms that plasticizers were uniformly distributed in PLA matrix.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Poly (Lactic acid); Poly (Butylene Succinate) (PBS); Poly (Ethylene Glycol) (PEG); Ricinoleic acid (R.ACID); Plasticizers